2020
DOI: 10.14311/ctj.2019.3.01
|View full text |Cite
|
Sign up to set email alerts
|

The Time Delay of Air/Oxygen Mixture Delivery After the Change of Set Fio2: An Improvement of a Neonatal Mathematical Model

Abstract: <p>Oxygen therapy is an essential treatment of premature infants suffering from hypoxemia. Normoxemia is maintained by an adjustment of the fraction of oxygen (FiO<sub>2</sub>) in the inhaled gas mixture that is set manually or automatically based on peripheral oxygen saturation (SpO<sub>2</sub>). Automatic closed-loop systems could be more successful in controlling SpO<sub>2</sub> than traditional manual approaches. Computer models of neonatal oxygen transport have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…We validated our concept using the full spectrum of available non-invasive (CPAP) ventilators with recommended interfaces across the full spectrum of adjustable pressures (flow rates), including the low nCPAP which admittedly has little clinical relevance. The measured delays without O 2 -FS matched those measured in our earlier study ( 16 ). It could be concluded that the connection of the system in the off state does not affect the normal function of the CPAP ventilatory support.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…We validated our concept using the full spectrum of available non-invasive (CPAP) ventilators with recommended interfaces across the full spectrum of adjustable pressures (flow rates), including the low nCPAP which admittedly has little clinical relevance. The measured delays without O 2 -FS matched those measured in our earlier study ( 16 ). It could be concluded that the connection of the system in the off state does not affect the normal function of the CPAP ventilatory support.…”
Section: Discussionsupporting
confidence: 86%
“…This study demonstrates that there is a feasible technical solution to the problem of the delay of oxygen distribution to a neonate after a change in a set FiO 2 . Previous studies found a significant delay between the change in the set FiO 2 and the actual oxygen delivery to neonates ( 16 , 17 ). However, we demonstrated that a system with a controlled electromechanical valve that delivers extra oxygen directly to the point where a non-invasive ventilatory support interface connects to a ventilator circuit reduces the delay of oxygen distribution to the neonate significantly.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations